Aproximación al tratamiento lexicográfico de verbos causativos de percepción en el Diccionario del Español Actual - Gutiérrez Fuentes, Gretel (2018)
Although dictionaries of valences and those of regime and construction are the best to recreate syntactic information, we recognize that dictionaries are useful not only to provide tools for decoding, but also to contribute to language codification. For this purpose, news about the possible combination of elements are of interest for this work, —and especially applied to verbs—, those related to transitivity and intransitivity, thelexicographic contour and the type of frequent definition. We study the lexicographic treatment of some causative verbs of perception in the Diccionario del español actual (DEA). The analysis of the lexicographic articles of this type of verbs revealed that it is possible to find transitive and intransitive uses, examples of causative alternation, besides, that the lexicographic contour tends to be integrated and heterogeneous especially in the factitive ones with the verb hacer, which were the most frequent. It was verified that ver is used in most of the definitions, referred to the visual perception, as semantic head in the definitional phrases.